Writing DNP clinical case narratives : demonstrating and evaluating competency in comprehensive care - Smolowitz, Janice; Honig, Judy; Reinisch, Courtney (Springer Pub. Co. : Columbia University School of Nursing, 2010)
This portfolio presents intimate case study narratives, providing an in-depth account of DNP best practices for clinical practice. The book covers important topics such as the development of DNP clinical competencies, performance objectives, utilizing evidence-based practice, a DNP approach to adolescent care, caring for the chronically ill, mental health care, adult health care, and many more. The main purpose of this book is to provide DNP faculty and students with a reliable and detailed guide to use when implementing a format to document care provided. The case narratives presented in this.